2007
DOI: 10.1002/bit.21720
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids for aqueous two‐phase extraction and stabilization of enzymes

Abstract: The ionic liquid (IL) Ammoeng110 contains cations with oligoethyleneglycol units and was found to be highly effective for the formation of aqueous two-phase systems (ATPS) that can be used for the biocompatible purification of active enzymes. Above critical concentrations of the IL and an inorganic salt in aqueous solution, phase separation takes place resulting in the formation of an IL-enriched upper and a salt-enriched lower phase. For the optimization of the composition of IL-based ATPS with regard to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
138
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(141 citation statements)
references
References 38 publications
1
138
1
1
Order By: Relevance
“…Xu and co-workers 183,185 utilized the conductorlike screening model for real solvents (COSMS-RS) to derive various parameters (such as misfit, H-bonding and van der Waals interaction energy) to understand the multiple interactions in ILs; the model also provides guidance in designing the structures of cations and anions. 190 The Kragl group 191 found that an IL in the Ammoeng family -Ammoeng 110 ( Fig. 5) -is quite effective in forming aqueous two-phase (ATP) for the purification of active enzymes (two different alcohol dehydrogenases); the IL is capable of stabilizing the enzymes and enhancing the solubility of hydrophobic substrates.…”
Section: Manipulation/design Of Il Structuresmentioning
confidence: 99%
“…Xu and co-workers 183,185 utilized the conductorlike screening model for real solvents (COSMS-RS) to derive various parameters (such as misfit, H-bonding and van der Waals interaction energy) to understand the multiple interactions in ILs; the model also provides guidance in designing the structures of cations and anions. 190 The Kragl group 191 found that an IL in the Ammoeng family -Ammoeng 110 ( Fig. 5) -is quite effective in forming aqueous two-phase (ATP) for the purification of active enzymes (two different alcohol dehydrogenases); the IL is capable of stabilizing the enzymes and enhancing the solubility of hydrophobic substrates.…”
Section: Manipulation/design Of Il Structuresmentioning
confidence: 99%
“…IL-based ABS have been used for the extraction of proteins and enzymes, while demonstrating to provide higher extraction efficiencies than the traditional PEG-based ABS [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Alkylimidazolium-based ILs combined with phosphate-based salts were the most widely investigated phase-forming components of ABS [15].…”
Section: Introductionmentioning
confidence: 99%
“…The initial interest on ILs as alternative extractive fluids results from their physical and chemical advantages, namely negligible flammability and vapour pressure, high solvation ability, high chemical stability, high selectivity, and easiness in recovering and recycling them [25][26][27][28][29]. Moreover, it was already shown that adequate ILs do not significantly inactivate enzymes ensuring thus their structural integrity and enzymatic activity [5,27].…”
Section: Introductionmentioning
confidence: 99%